Home literacy environment and early reading skills in Japanese Hiragana and Kanji during the transition from kindergarten to primary school - Tanji, Takayuki; Inoue, Tomohiro (Frontiers in Psychology, 2023)
We examined the reciprocal associations between home literacy environment (HLE) and children’s early reading skills in syllabic Hiragana and morphographic Kanji in a sample of Japanese parent-child dyads. Eighty-three children were followed from kindergarten to Grade 3 and tested on Hiragana reading accuracy in kindergarten, Hiragana word reading fluency in kindergarten and Grade 1, and Kanji reading accuracy in Grade 1 to Grade 3. Their parents answered a questionnaire about HLE (parent teaching [PT] in Hiragana and Kanji, shared book reading [SBR], and access to literacy resources [ALR]), parents’ needs for early literacy support by teachers, parents’ expectations for children’s reading skills, parents’ worry about children’s homework, and mother’s education level. Results showed first that ALR, but not PT and SBR, was associated with reading skills in Hiragana and Kanji. Second, whereas Hiragana reading in kindergarten was not associated with PT in Hiragana in kindergarten, it negatively predicted PT in Hiragana in Grade 1. However, Kanji reading accuracy was not associated with PT in Kanji across Grades 1 to 3. Third, parents’ worry was negatively associated with children’s reading performance across Grades 1 to 3 but positively associated with PT in Hiragana and Kanji. Finally, while parents’ expectations were positively associated with children’s reading performance across Grades 1 to 3, they were negatively associated with PT in Hiragana and Kanji in Grades 1 and 2. These results suggest that Japanese parents may be sensitive to both their children’s reading performance and social expectations for school achievement and adjust their involvement accordingly during the transition period from kindergarten to early primary grades. ALR may be associated with early reading development in both Hiragana and Kanji.